Within and Across Language Predictors of Word Learning Processes in Dual Language Learners. Issue 1 (10th August 2020) - Pace, Amy; Luo, Rufan; Levine, Dani; Iglesias, Aquiles; de Villiers, Jill; Golinkoff, Roberta M.; Wilson, Mary S.; Hirsh‐Pasek, Kathy
Abstract : This study investigated the relation between Dual Language Learners' ( N = 90) vocabulary and grammar comprehension and word learning processes in preschool (aged 3‐through‐5 years). Of interest was whether: (a) performance in Spanish correlated with performance in English within each domain; and (b) comprehension predicted novel word learning within and across languages. Dual‐language experience was evaluated as a potential moderator. Hierarchical linear modeling revealed stronger predictive associations within each language than across languages. Across languages, results varied by experience and domain. Structural sensitivity theory suggests exposure to two languages heightens awareness of parameters along which languages vary and provides a framework for interpreting complex associations within and across languages. Knowledge from one language may influence learning in both.